2019
DOI: 10.1038/s41598-019-42513-2
|View full text |Cite
|
Sign up to set email alerts
|

Buffalo milk transcriptome: A comparative analysis of early, mid and late lactation

Abstract: The expression of genes and their regulation during lactation in buffaloes remains less understood. To understand the interplay of various genes and pathways, the milk transcriptome from three lactation stages of Murrah buffalo was analyzed by RNA sequencing. The filtered reads were mapped to the Bubalus bubalis as well as Bos taurus reference assemblies. The average mapping rate to water buffalo and Btau 4.6 reference sequence, was 75.5% and 75.7% respectively. Highly expressed genes (RPKM > 3000), throughout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 45 publications
2
29
0
Order By: Relevance
“…The FTH1 gene encodes for the heavy subunit of ferritin. The presence of ferritin in cow's and buffalo's milk has been reported [40,47].…”
Section: Gwas and Gsa Of Maternal Composite Traits At Weaningmentioning
confidence: 99%
See 3 more Smart Citations
“…The FTH1 gene encodes for the heavy subunit of ferritin. The presence of ferritin in cow's and buffalo's milk has been reported [40,47].…”
Section: Gwas and Gsa Of Maternal Composite Traits At Weaningmentioning
confidence: 99%
“…Many GO terms related to protein metabolism and transport and fatty asides metabolism were identified. Recently, in a transcriptome analysis study on buffalo milk, protein metabolism (GO:0019538) pathway identified as a significant term [47]. Changes in the amount of fatty acid synthesis during late-pregnancy and lactation have been long and newly reported for a variety of species including the rat, rabbit, pig, and cow [48,49].…”
Section: Gwas and Gsa Of Maternal Composite Traits At Weaningmentioning
confidence: 99%
See 2 more Smart Citations
“…To our knowledge, there have been no studies that have reported direct sequencing of porcine whole milk samples. In fact, only six livestock RNA-sequencing (RNA-Seq) studies have reported sequencing of milk, including three in cattle [9,21,22], one in goat [23], one in sheep [24], and one in buffalo [25]. The emphasis of these studies was gene expression related to the lactation process, and as such, milk somatic cells were sequenced as a proxy for the mammary gland tissue [26].…”
mentioning
confidence: 99%